Proof: Pre Extend Example
Let's prove the following theorem:
reverse and insert [ 4, [ 0, [ ] ] ] to the beginning of [ 2, [ ] ] = [ 0, [ 4, [ 2, [ ] ] ] ]
Proof:
# | Claim | Reason |
---|---|---|
1 | reverse and insert [ 4, [ 0, [ ] ] ] to the beginning of [ 2, [ ] ] = reverse and insert [ 0, [ ] ] to the beginning of [ 4, [ 2, [ ] ] ] | reverse and insert [ 4, [ 0, [ ] ] ] to the beginning of [ 2, [ ] ] = reverse and insert [ 0, [ ] ] to the beginning of [ 4, [ 2, [ ] ] ] |
2 | reverse and insert [ 0, [ ] ] to the beginning of [ 4, [ 2, [ ] ] ] = reverse and insert [ ] to the beginning of [ 0, [ 4, [ 2, [ ] ] ] ] | reverse and insert [ 0, [ ] ] to the beginning of [ 4, [ 2, [ ] ] ] = reverse and insert [ ] to the beginning of [ 0, [ 4, [ 2, [ ] ] ] ] |
3 | reverse and insert [ ] to the beginning of [ 0, [ 4, [ 2, [ ] ] ] ] = [ 0, [ 4, [ 2, [ ] ] ] ] | reverse and insert [ ] to the beginning of [ 0, [ 4, [ 2, [ ] ] ] ] = [ 0, [ 4, [ 2, [ ] ] ] ] |
4 | reverse and insert [ 4, [ 0, [ ] ] ] to the beginning of [ 2, [ ] ] = reverse and insert [ ] to the beginning of [ 0, [ 4, [ 2, [ ] ] ] ] | if reverse and insert [ 4, [ 0, [ ] ] ] to the beginning of [ 2, [ ] ] = reverse and insert [ 0, [ ] ] to the beginning of [ 4, [ 2, [ ] ] ] and reverse and insert [ 0, [ ] ] to the beginning of [ 4, [ 2, [ ] ] ] = reverse and insert [ ] to the beginning of [ 0, [ 4, [ 2, [ ] ] ] ], then reverse and insert [ 4, [ 0, [ ] ] ] to the beginning of [ 2, [ ] ] = reverse and insert [ ] to the beginning of [ 0, [ 4, [ 2, [ ] ] ] ] |
5 | reverse and insert [ 4, [ 0, [ ] ] ] to the beginning of [ 2, [ ] ] = [ 0, [ 4, [ 2, [ ] ] ] ] | if reverse and insert [ 4, [ 0, [ ] ] ] to the beginning of [ 2, [ ] ] = reverse and insert [ ] to the beginning of [ 0, [ 4, [ 2, [ ] ] ] ] and reverse and insert [ ] to the beginning of [ 0, [ 4, [ 2, [ ] ] ] ] = [ 0, [ 4, [ 2, [ ] ] ] ], then reverse and insert [ 4, [ 0, [ ] ] ] to the beginning of [ 2, [ ] ] = [ 0, [ 4, [ 2, [ ] ] ] ] |
Comments
Please log in to add comments